Analisis Kinerja Guru Memperhatikan Iklim Organisasi, Lingkungan dan Kepuasan Kerja (Studi pada Sekolah Dasar Wilayah Kecamatan Samalanga Kabupaten Bireuen) - Azmi, Azmi; Kamaruddin, Kamaruddin (peusangan, 2024)
The research aims to study and analyze teacher performance, involving internal and external factors, namely organizational climate, environment and job satisfaction. Case study of state elementary school teachers in the Samalanga District, Bireuen Regency. Using associative descriptive methods with a path analysis approach. Taking a sample of 70 teachers, collecting data through questionnaires. The results of the teacher performance analysis prove: (a). There is a correlation between organizational climate, environment and job satisfaction, each of 0.68; 0.66 and 0.65. (b). Teacher performance is influenced, both directly and indirectly, by school organizational climate factors by 26.6%. (c). Teacher performance is influenced, both directly and indirectly, by work environment factors by 38.2%. (d). Teacher performance is influenced, both directly and indirectly, by the job satisfaction factor of 9.6%.